National Atlas of Arctic: structure and creation approaches - N. S. Kasimov; V. M. Kotlyakov; A. N. Chilingarov; D. M. Krasnikov; V. S. Tikunov (Лëд и снег, 2015)
On the instructions of President and Government of the Russian Federation, works for development of National Atlas of Arctic are started in the country. In this article the authors present their ideas from viewpoint of geographers who are well experienced in the field of cartographic works. A structure of future Atlas and lines of approaches to its development are proposed. The totality of experiences of preparation of other geographical atlases in both, the USSR and Russia, as well as the latest achievements of cartography, aerospace sources and GIS-technologies are recommended to be used. The National Atlas of Arctic is understood as a collection of knowledge of spatial-temporal information about geographical, ecological, economic, historical-ethnographic, cultural and social features of the Arctic. This cartographic model of the territory is designed for using in a wide range of scientific, managing, economic, defensive and social activities. A hard copy of the atlas is intended to be used as scientific-reference publication while its electronic version will make it possible to renovate its content and to improve it by means of actualization according to various directions of its practical use 16 sections proposed in a draft of the Atlas content are as follows: introductory, geological structure, relief, mineral resources, environment evolution, climate, land waters, seas, seashores, snow cover, glaciers, permafrost, soils, flora and fauna, state of the environment and the Nature protection, population, economics, and prospects for future. The popular-scientific edition of the Atlas is intended for use by wide circle of readers and also as a textbook for all levels of education. Presentation of material in the Atlas should combine a high scientific level and accessible language. In a popular form it will clarify traditions of careful treatment to the Nature and the nature-protective ethics of religious confessions of local people. Touristic maps will serve as guides for the Arctic with its bio-landscape and cultural diversity. Content of the Atlas should meet requirements of education standard in the field of geography. Ten sections are proposed for this version of the Atlas: introductory, geological structure, relief and resources, climate, permafrost and glaciers, land waters, seas of the Russian part of the Arctic, its flora and fauna, soils, population and economics, and conclusion Scientific and social results of the Atlas publication together with editorial and advertizing effects are demonstrated. Proposals for a format, scales of maps and type of edition are given, and potential participants of this project are indicated.